Uniformity coefficients in low-flow sprayers with different arrangements and height - Rodrigues, Leoncio Gonçalves; Nery, Aparecida Rodrigues; Sousa, Francisco Rondynelle Rodrigues; Rodrigues, Luis Nery (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
In sprinkler irrigation, the water is precipitated artificially. In this system, the distribution efficiency is subject to the characteristics of the sprinkler, pressure, operating flow, external factors such as wind and temperature, type of arrangement and stem height. In view of the above, this study aimed to evaluate the Coefficient of Uniformity Christiansen - CUC, Coefficient of Uniformity of Distribution - CUD and Coefficient of Statistical Uniformity - CUE in low flow sprinklers under the quadrangular, triangular and rectangular arrangements, for height of rod of 1,50 and 2,00 m under low pressure of 10 mca. The NDJ 5022 sprinkler presented coefficients up to 80% for all arrangements and overlays, with a triangular arrangement that presents the best installation cost.